2009
DOI: 10.1007/s10532-009-9304-9
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline biodegradation and its nitrogen transformation pathway by a Pseudomonas sp. strain

Abstract: A Pseudomonas sp. strain, which can utilize quinoline as its sole carbon, nitrogen and energy source, was isolated from activated sludge in a coking wastewater treatment plant. Quinoline can be degraded via the 8-hydroxycoumarin pathway. We quantified the first two organic intermediates of the biodegradation, 2-hydroxyquinoline and 2,8-dihydroxyquinoline. We tracked the transformation of the nitrogen in quinoline in two media containing different C/N ratios. At least 40.4% of the nitrogen was finally transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 34 publications
0
25
2
Order By: Relevance
“…The Luria-Bertani (LB) medium [11] was used for bacteria enrichment and maintenance. The mineral salt medium (MSM), which does not contain N source as described by Bai et al [12], was used as the basic ingredient for the bacterial degradation and transformation. The carbazole was dissolved in DMSO (30 g/L) and added to the MSM as the sole degradable carbon, nitrogen, and energy source in the biodegradation experiments.…”
Section: Mediamentioning
confidence: 99%
“…The Luria-Bertani (LB) medium [11] was used for bacteria enrichment and maintenance. The mineral salt medium (MSM), which does not contain N source as described by Bai et al [12], was used as the basic ingredient for the bacterial degradation and transformation. The carbazole was dissolved in DMSO (30 g/L) and added to the MSM as the sole degradable carbon, nitrogen, and energy source in the biodegradation experiments.…”
Section: Mediamentioning
confidence: 99%
“…Quinoline and its derivates are found widely in coal tar, oil shale, and petroleum, and serve as intermediates and solvents in many industries (Bai et al 2010). The existence of these compounds has a great negative impact on human health and environmental quality because of the toxic, mutagenic and carcinogenic properties of these compounds.…”
mentioning
confidence: 99%
“…3,4 In previous studies, [4][5][6] it was found that certain bacteria are effective in decomposing Q. It was also suggested that the biochemical conversion of Q into 2-hydroxyquinoline (HQ) 7,8 occurs in the first step of the metabolic pathways that are affected by the intermediates. 9 However, the mechanisms of Q degradation in bacteria remain unclear due to lack of quantitative information about intermediate and final products of the biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…3,7,[10][11][12] However, sophisticated or intensive sample pretreatment procedures are required for using these methods. For example, sample filtration must be used to remove the precipitates or particles from the sample solution before HPLC analysis.…”
Section: Introductionmentioning
confidence: 99%